'Unfit for human consumption': a study of the contamination of formula milk fed to young children in East Java, Indonesia. Issue 10 (7th August 2017) - Gibson, Sarah; Sahanggamu, Daniel; Fatmaningrum, Dewi; Curtis, Val; White, Sian
Abstract: Objectives: To examine levels of bacterial contamination in formula feeding bottles in Sidoarjo, East Java, and to assess the preparation practices that may have been responsible. Methods: A cross‐sectional study was conducted among 92 randomly selected households with children under the age of two who were bottle‐fed formula. In each household, we carried out video observation of mothers/caregivers preparing bottles, and examined samples of formula for coliform bacteria and Escherichia coli ( E. coli ). In‐depth interviews were conducted with a subsample of 20 mothers. Results: A total of 88% of the formula feeds were contaminated with total coliforms at a level >10 MPN/ml, and 45% contained E. coli . These feeds were defined as 'unfit for human consumption'. In the video observations, none of the mothers complied with all five WHO‐recommended measures of hygienic formula feed preparation. Only two mothers washed their hands with soap prior to formula preparation. Most mothers also failed to clean or sterilise the bottle and clean the preparation area. In‐depth interviews confirmed that such suboptimal hygiene practices were common. Conclusion: The high levels of contamination found highlight that bottles are an important faecal‐oral exposure pathway resulting from poor hygiene practices during bottle preparation.